Peran Partisipasi Masyarakat dalam Proses Perencanaan Wilayah: Studi Kasus di Desa Butu Kecamatan Tilongkabila - Modanggu, Intan; Kuuna, Wahyudin; Pambudi, Moch. Rio; Eraku, Sunarty Suly (PT. Pubsains Nur Cendekia, 2023)
Regional planning has a very crucial role in improving the quality of life of the population, advancing the agricultural sector, protecting the ecosystem, and designing infrastructure that suits the needs of local communities. However, rural communities are often ignored or less involved in the regional planning process, which can result in an imbalance between the resulting policies and actual needs on the ground. The aim of this research is to analyze the role of community participation in the regional planning process in Butu Village. This research uses descriptive methods with qualitative analysis. Instrument indicators include: 1) the existence of groups to accommodate community participation; 2) the ability of the community to be involved in the process; and 3) there are community activities to express opinions in the decision-making process. Research findings show that the Butu Village community is actively involved in the development planning process through mechanisms such as the Development Planning Conference (MUSREMBANG) with government officials.